Effect of Organophosphate, Monocrotophos on Behavioural, Haematological, Histological and Biochemical Indices in the Subtropical Catfish Heteropneustes fossilis (Bloch, 1794) - PATTNAIK, S.T.; SAMAL, SURYASIKHA; MISHRA, C.S.K.; GHOSH, PULAK; MUDULI, NISHIGANDHA; BISWAL, MANISHA; ACHARYA, PRATIK; HAQUE, RAMJANUL; KUMAR, RAJESH; SUNDARAY, JITENDRA KUMAR (Journal of the Indian Society of Coastal Agricultural Research, 2022)
A study was conducted to evaluate the impact of acute sub-lethal toxicity of monocrotophos on behavioural, biochemical, haematological and histopathological changes in Heteropneustes fossilis (49.53±0.71 g). Probit analysis showed the 96 h LC50 of monocrotophos for H. fossilis was 20 ppm. Followed by the LC50 value, sub-lethal concentrations for acute exposure of monocrotophos were 3 ppm in T1, 6 ppm in T2 and 8 ppm in T3 for 72 h of the experimental period. The behavioural responses observed in treated fish were: erratic movement, imbalance in swimming, surfacing, and hyperactivities. A gradual reduction in total RBC count, haemoglobin, monocyte, and basophil contents were observed with an increased concentration of monocrotophos. On other hand, the total WBC count, neutrophil, basophil and blood ESR showed reversed trend (p